The perceptions of key stakeholders of the roles of specialist and advanced nursing and midwifery practitioners. (12th July 2017) - Casey, Mary; O'Connor, Laserina; Nicholson, Emma; Smith, Rita; O'Brien, Denise; O'Leary, Denise; Fealy, Gerard M; Mcnamara, Martin S; Stokes, Diarmuid; Egan, Claire
Abstract: Aim: To explore the perceptions of key stakeholders of the roles of specialist and advanced nursing and midwifery practitioners. Background: There is evidence that the contribution of these roles to patient care is poorly understood. Design: This research took place over 2 months in 2015 and is part of a larger study involving a rapid review to inform policy development on the specialist and advanced nursing and midwifery practice in Ireland. As an added value, a qualitative element involving thematic analysis was undertaken with key stakeholders. Methods: A phenomenological qualitative study was conducted incorporating semi‐structured interviews with key stakeholders ( n = 15). Purposive sampling with maximum diversity was used to recruit a wide range of perspectives. Findings: Participant's perspectives led to seven themes: Impact of these roles; role preparation, experience and organizational support; specialist and advanced practice roles in an interdisciplinary context; different folks but not such different roles; impact of specialist and advanced practice roles on patient outcomes; barriers and facilitators to enacting specialist and advanced practice roles; future development of these roles. Conclusion: There is acknowledgement of the positive impact of specialist and advanced practitioners; however, the evidence is currently not conclusive. Preparation for these roles needs to reflect changes in the calibre of today's professional applicants, and organizational support is paramount to their successful execution. The contribution of their activity to patient outcome needs to be made visible to enhance these roles and to justify the development of new roles across a variety of healthcare areas.